Nephrotoxic contaminants in drinking water and urine, and chronic kidney disease in rural Sri Lanka - Rango, T.; Jeuland, M.; Manthrithilake, Herath; McCornick, Peter G. (Elsevier, 2015)
Chronic kidney disease of unknown (“u”) cause (CKDu) is a growing public health concern in Sri Lanka. Prior research has hypothesized a link with drinking water quality, but rigorous studies are lacking. This study assesses the relationship between nephrotoxic elements (namely arsenic (As), cadmium (Cd), lead (Pb), and uranium (U)) in drinking water, and urine samples collected from individuals with and/or without CKDu in endemic areas, and from individuals without CKDu in nonendemic areas. All water samples – from a variety of source types (i.e. shallow and deep wells, springs, piped and surface water) – contained extremely low concentrations of nephrotoxic elements, and all were well below drinking water guideline values. Concentrations in individual urine samples were higher than, and uncorrelated with, those measured in drinking water, suggesting potential exposure from other sources. Mean urinary concentrations of these elements for individuals with clinically diagnosed CKDu were consistently lower than individuals without CKDu both in endemic and nonendemic areas. This likely stems from the inability of the kidney to excrete these toxic elements via urine in CKDu patients. Urinary concentrations of individuals were also found to be within the range of reference values measured in urine of healthy unexposed individuals from international biomonitoring studies, though these reference levels may not be safe for the Sri Lankan population. The results suggest that CKDu cannot be clearly linked with the presence of these contaminants in drinking water. There remains a need to investigate potential interactions of low doses of these elements (particularly Cd and As) with other risk factors that appear linked to CKDu, prior to developing public health strategies to address this illness.